TRAUMA HEALING DALAM PERSPEKTIF DAKWAH NABI YUSUF AS DI ERA KONTEMPORER - Moh Syahri Sauma; Hendar Ardiansyah (An-Nida' : Jurnal Komunikasi dan Penyiaran Islam, 2025)
Trauma is an emotional response to distressing events such as accidents, disasters, or violence. Its effects are both physical and mental, often leading to post-traumatic stress disorder (PTSD). Trauma healing plays a critical role in recovering individuals from such experiences. In the Qur'an, the story of Prophet Yusuf (Joseph) provides spiritual and practical guidance on trauma healing, particularly in Surah Yusuf verse 21. Prophet Yusuf's story includes traumatic experiences such as being cast into a well by his brothers, falsely accused by Zulaikha, and imprisoned. Through trauma healing approaches outlined in his story, like dignity restoration and empowerment by Qithfir and Zulaikha, Yusuf overcame emotional scars and rebuilt his life. These principles align with modern trauma healing strategies, emphasizing the importance of respecting victims' dignity and supporting their future development. The story of Prophet Yusuf demonstrates the importance of a holistic approach to trauma healing, encompassing emotional, spiritual, and physical recovery. As the best narrative in the Qur'an, it offers valuable lessons on resilience, forgiveness, and recovery. These principles remain relevant in contemporary contexts, aiding individuals in overcoming trauma and creating a brighter future.